2015
DOI: 10.1097/ta.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Management of children with solid organ injuries after blunt torso trauma

Abstract: Prognostic/epidemiologic study, level III; therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 37 publications
(27 reference statements)
10
53
5
Order By: Relevance
“…Similar to what was previously reported in other series 1,3,6,7,15,23,27 , pedestrian-like traffic accidents are the predominant trauma mechanism in the hepatic and splenic injuries due to closed trauma in our study group, followed by falls from high heights in second place and others less common causes, as trauma on bicycle or skateboards, trauma with blunt objects among others. The most affected group was the 5 to 10 years old children.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Similar to what was previously reported in other series 1,3,6,7,15,23,27 , pedestrian-like traffic accidents are the predominant trauma mechanism in the hepatic and splenic injuries due to closed trauma in our study group, followed by falls from high heights in second place and others less common causes, as trauma on bicycle or skateboards, trauma with blunt objects among others. The most affected group was the 5 to 10 years old children.…”
Section: Discussionsupporting
confidence: 77%
“…Certain conditions have been associated with this fact, such as severe hepatic or splenic lesions (IV-V), since the more severe the lesion, the greater the probability of hemodynamic instability or association with injury to other organs, the hemoperitoneum abundant (3-4 quadrants), pseudoaneurysms and/or leakage of radiological contrast IV in CAT 1,[12][13][14]24,27,28,36 . However, other series have shown that 61-86% of grade IV lesions and 32-77% of grade V lesions (in the absence of hemodynamic instability) have been treated conservatively 6,7,[12][13][14][15]22 , and it does not matter the age, gender, mechanism of trauma and degree of injury 13,17 , because it is hemodynamic instability the one that does not show improvement after 6 hours of adequate resuscitation, which predicts almost a 100% of correlation between the need for laparotomy and splenectomy in children with closed trauma spleen 29 . The above is clear, a periodic evaluations by trained personnel are necessary in order to allow the early detection of the surgical interventions need and to identify patients at high risk, avoiding failure of NOM 6,7,[12][13][14][15]23,27,[29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations